THU0219 FIRST-INHUMAN STUDY OF SAFETY, PHARMACOKINETICS AND PHARMACODYNAMICS OF IRAK1/4 INHIBITOR R835 IN HEALTHY SUBJECTS. (2nd June 2020) - Yan, L.; Tong, S.; Absalom, A.; Daas, I. D.; Park, G.; Taylor, V.; Chow, D.; Lee, M.; Zheng, H.; Chow, A.
Abstract : Background: Toll-Like Receptors (TLR) and Interleukin-1 Receptors (IL-1R) play a critical role in the innate immune response as microbial and tissue damage sensors, providing a bridge between the innate and adaptive immunity. Interleukin receptor associated kinases (IRAK) 1 and 4 are serine/threonine kinases that are essential for signaling downstream of most TLRs and IL-1Rs and the resulting production of pro-inflammatory cytokines. Suppression of TLR and IL-1R signaling through inhibition of IRAK1/4 kinases is a promising therapeutic approach for the treatment of inflammatory and autoimmune diseases. We have identified a potent and selective IRAK1/4 inhibitor (R835) that showed dose-dependent inhibition of lipopolysaccharide (LPS, a TLR4 agonist), and IL-1β induced serum cytokines in mice. R835 prevented disease onset and progression in multiple rodent models of inflammatory diseases, including arthritis and lupus models. Objectives: The aim of this FIH study was to characterize the safety, pharmacokinetics (PK) and pharmacodynamics (PD) of R835 after single or multiple dose oral administrations. Methods: This study was a randomized, placebo-controlled, double-blind Phase 1 study in healthy subjects in three parts: single ascending doses (20 mg-1920 mg, Part A) with food effect in a separate cohort (480 mg), multiple ascending doses (120 mg and 960 mg, BID, Part B) with a caffeine interaction (960 mg cohort), and an intravenous LPS challenge test at 240 mg oral dose of R835 (Part C). Results: Single doses of up to 480 mg R835 in organic solution, single doses of up to 1920 mg R835 as capsule, multiple doses of 120 mg R835 Q12H (organic solution), and 960 mg R835 Q12H (capsule) were safe and well tolerated. All R835 related adverse events (AEs) were mild in intensity and reversible, and mostly associated with the higher doses of R835 in the organic solution. The most common AEs were headache and gastrointestinal disturbance. The PK of R835 was linear and dose proportional in exposure over the dose range studied. A nominal level of accumulation in plasma achieved rapidly upon repeated BID administrations with steady-state essentially attained in 2 days. A high-fat meal with the capsule formulation resulted in slow rate of absorption but had no effect on the extent of absorption. There was no effect of R835 on metabolism of caffeine (P450 CYP1A2 prototype substrate). In the LPS challenge test, R835 profoundly inhibited the acute release of cytokines, including TNF-α, IL-6, IL-8, MIP1α and MIP1β, but had no impact on CRP release. Conclusion: R835 was well tolerated after single or multiple dose administrations. The most common AEs were headache and gastrointestinal disturbance. For both of the formulations tested, the PK of R835 was linear and exposure was dose proportional with rapid steady-state attainment following BID administration. There was no drug-drug interaction by use of caffeine as the protype substrate. R835 inhibited the LPS induced release of cytokines in the serum, including TNF-α, IL-6, IL-8, MIP1α and MIP1β, mirroring preclinical data in mice. The desirable PK and safety profile combined with proof of mechanism, as demonstrated by inhibition of cytokine release, support progression of R835 into Phase II clinical development as an agent for the treatment of inflammatory and autoimmune diseases. Disclosure of Interests: Lucy Yan Shareholder of: Amgen, Rigel, Employee of: Amgen, Rigel, Sandra Tong Shareholder of: Rigel, Employee of: Rigel, Anthony Absalom: None declared, Izaak den Daas: None declared, Gary Park Shareholder of: Rigel Pharmaceuticals, Employee of: Rigel Pharmaceuticals, Vanessa Taylor Shareholder of: Rigel Pharmaceuticals, Employee of: Rigel Pharmaceuticals, Donna Chow Shareholder of: Rigel, Employee of: Rigel, Meng Lee Shareholder of: Rigel, Employee of: Rigel, Hanzhe Zheng Shareholder of: Rigel, Employee of: Rigel, Andrew Chow Shareholder of: Rigel, Employee of: Rigel